Measurement of above-ground carbon stocks of roadside agroforestry plantation at Sadar upazila of Mymensingh district in Bangladesh (Journal of the Bangladesh Agricultural University, 2024)
In this research, floristic composition and above-ground carbon stocks of all woody species in roadside plantations under Sadar Upazila of Mymensingh District were studied. A total of 280 sample plots of 2 m×10 m size was selected following systematic random sampling in a zigzag manner on both sides along the roadside plantation were measured. The result showed that a total of 29 species of 14 families were recorded where the most common species are Acacia auriculiformis, Swietenia sp, and Artocarpus heterophyllus. It was found that Albizia saman, Albizia lebbeck and Swietenia sp comprises 71% of total aboveground carbon of which Albizia saman occupies the highest (50%) amount among the tree species in the study area. Similarly, Swietenia sp in the case of tree seedlings, Cocos nucifera in case of palm species and Acacia auriculiformis deadwood species occupy the highest amount of above-ground carbon (68, 48 and 73%) respectively in the study area. The study revealed that the total carbon stock measured in the roadside plantation were 2554.27 Mg/ha where tree occupies the highest (2078.44 Mg/ha) amount of carbon stock and the lowest (2.85 Mg/ha) in seedlings/saplings in the study area. The results indicate that two attributes such as tree basal area and stand density/ha are strongly related to above-ground carbon stocks, but stand mean height is weakly related. Therefore, the study recommends that the above-ground carbon stocks would increase with the increase of planting trees having greater DBH, basal area and stand density in the roadside areas.J Bangladesh Agril Univ 18(2): 252–259, 2020https://doi.org/10.5455/JBAU.91198